Aktivitas Remaja dalam Memakmurkan Masjid - Hasna Nurmila; Indri Rachmawati (Bandung Conference Series: Communication Management, 2024)
Abstract. In the context of organizational communication, "output" refers to the results or output of the communication process which can be in the form of decisions, actions, or information that is produced and influences the organization. For example, communication between the chairman and members of a mosque youth organization can produce output in the form of decisions that can influence the running of the organization, such as changes to create prosperity for the mosque. The Daarul Muhajir mosque youth organization produces outputs such as forming and managing an Islamic event program in the mosque environment so that it can attract the attention of the surrounding environment as a means of education and spiritual development. The aim of the mosque youth organization is to mobilize the community and youth in the environment to be better, especially in the religious sector. The research method of this study uses a descriptive approach by collecting qualitative data in the form of interviews, documentation and observation. The teenage population of the Daarul Muhajir mosque is 20 people. Sampling used purposive sampling technique. The results of this research show that the output of the Daarul Muhajir mosque youth organization is in the form of Islamic events which are able to encourage the creation of mosque prosperity in the environment. Abstrak. Pada konteks komunikasi “output” mengacu pada hasil atau keluaran dari proses komunikasi yang dapat berupa keputusan, tindakan, atau informasi yang dihasilkan dan mempengaruhi organisasi. Misalnya, komunikasi antar ketua dan anggota organisasi remaja masjid dapat menghasilkan output berupa keputusan yang dapat mempengaruhi jalannya organisasi, seperti perubahan agar terciptanya kemakmuran masjid. Organisasi remaja masjid Daarul Muhajir ini mengeluarkan output seperti membentuk dan mengelola program event Islami di lingkungan masjid agar dapat menarik perhatian lingkungan sekitar sebagai sarana edukasi dan pengembangan spiritual. Tujuan dari organisasi remaja masjid yaitu sebagai penggerak masyarakat dan remaja di lingkungan tersebut supaya lebih baik khususnya di bidang keagamaan. Metode penelitian dari penelitian ini menggunakan pendekatan deskriptif dengan pengambilan data kualitatif berupa wawancara, dokumentasi dan observasi. Populasi remaja masjid Daarul Muhajir berjumlah 20 orang. Pengambilan sampel menggunakan teknik purposive sampling. Hasil dari penelitian ini menunjukkan bahwa output dari organisasi remaja masjid Daarul Muhajir berupa event-event Islami yang mampu mendorong agar terciptanya kemakmuran masjid di lingkungan tersebut